2002
DOI: 10.1021/ja027860v
|View full text |Cite
|
Sign up to set email alerts
|

Polyhedral Oligomeric Silsesquioxanes:  A New Class of Amphiphiles at the Air/Water Interface

Abstract: Insoluble films of trisilanolisobutyl-POSS and octaisobutyl-POSS at the air/water interface are investigated by means of surface pressure - area per molecule isotherm (Pi - A) and Brewster angle microscopy (BAM). Analysis of the experimental results shows the partial cage molecule, trisilanolisobutyl-POSS, is a surface-active molecule that self-assembles into uniform monolayer upon compression; but the fully condensed cage molecule, octaisobutyl-POSS, is nonamphiphilic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
88
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 16 publications
4
88
1
Order By: Relevance
“…It is obvious from Figure 6 that Cy 8 T 8 molecules form multilayers even at low surface pressure (Π ≈ 0 mN m -1 ); thus, it is impossible to estimate a reasonable area per POSS molecule from the figure. This behavior is expected on the basis of previously reported data for octaisobutyl-POSS 23,24 and the completely hydrophobic character of Cy 8 T 8 . On the other hand, it is possible to estimate the area each cyclohexyl-substituted POSS cage occupies from Cy 7 T 7 (OH) 3 since these molecules form stable monolayers and feature nearly identical structures.…”
Section: Compression Isotherm Studies Of Peg Vs Poss-peg-posssupporting
confidence: 84%
“…It is obvious from Figure 6 that Cy 8 T 8 molecules form multilayers even at low surface pressure (Π ≈ 0 mN m -1 ); thus, it is impossible to estimate a reasonable area per POSS molecule from the figure. This behavior is expected on the basis of previously reported data for octaisobutyl-POSS 23,24 and the completely hydrophobic character of Cy 8 T 8 . On the other hand, it is possible to estimate the area each cyclohexyl-substituted POSS cage occupies from Cy 7 T 7 (OH) 3 since these molecules form stable monolayers and feature nearly identical structures.…”
Section: Compression Isotherm Studies Of Peg Vs Poss-peg-posssupporting
confidence: 84%
“…The uniform reflected area was attributed to liquid expanded phase, and the dots may consist of POSS nanocrystals because of their high aggregation property. 11,12 The BAM images of 4DEGNH DDSQ resemble those of 4DEGDDSQ. This result is quite different from that observed in the case of 2DEGDDSQ, which has two DEG units as the coronae.…”
mentioning
confidence: 94%
“…In this case, the results described as the effect of the thermal barrier and formation of interconnected layers were suggested in the incorporation of octafunctional POSS, i.e., an average of eight functional groups at the vertices of the cage. However, other studies using monofunctional POSS have demonstrated that the hybrid cages tend to exhibit amphiphilic features [12,14]. This observation was made based on the fact that POSS tends to form micelles to relieve the interfacial tension between the inorganic cages and the resin (which interact with the organic groups bonded at the vertices of the cages) [14].…”
Section: Introductionmentioning
confidence: 99%
“…This observation was made based on the fact that POSS tends to form micelles to relieve the interfacial tension between the inorganic cages and the resin (which interact with the organic groups bonded at the vertices of the cages) [14]. This difference in functionality could affect the response in thermal stability compared with the formation of layers [2,3,9] and micelles by POSS [12,14]. The aim of this work is to evaluate the influence of the formation of POSS (glicydilisobutyl-POSS) micelles on the thermal stability and the kinetic degradation of the epoxy resin.…”
Section: Introductionmentioning
confidence: 99%